Analisa Pengaruh Sosial Ekonomi terhadap Pendapatan Pedagang Kaki Lima di Pasar Induk Lambaro Kabupaten Aceh Besar - Munazar Munazar; Yuliana Yuliana; Yulfrita Adamy; Edi Saputra; Yunida Pangastuti (Jurnal Humaniora : Jurnal Ilmu Sosial, Ekonomi dan Hukum, 2022)
This research is partially and simultaneously to determine the effect of social factors and economic factors simultaneously on the income of street vendors at the Lambaro Main Market, Aceh Besar District. The research location is the Lambaro Main Market, Aceh Besar Regency, while the object of research is social and economic factors on the income of street vendors. The sampling technique method is simple random sampling. The data analysis method used in this research is multiple linear regression. The number of respondents in this study were 121 employees with a census sampling technique. The results of the study prove that simultaneously social and economic factors influence the increase in the income of street vendors at the Lambaro Main Market, Aceh Besar Regency with an Fcount of 47,313, while the Ftable at a significance level of = 5% is 3,110, then the results of the study show that partially the social factor variable with a regression coefficient value of 0.211 affects the income of street vendors at the Lambaro Main Market, Aceh Besar District and the results show that partially the economic factor variable with a regression coefficient value of 0.087 also affects the income of street vendors at the market. Parent Lambaro Aceh Besar District.